Combined myocardial deformation to predict cardiac resynchronization therapy response in nonischemic cardiomyopathy. - Yang, Ning; Liang, Zhao ‐ Guang; Wang, Zhao ‐ Jun; Liu, Hui; Chi, Chao; Tian, Yan ‐ Feng; Qi, Shu ‐ Han; Wang, Bi ‐ Yu; Han, Wei (Pacing & Clinical Electrophysiology, 2017)
Background 20-30% of patients do not benefit from cardiac resynchronization therapy (CRT) when the established selection criteria were applied. We hypothesized that a combined assessment of mechanical dyssynchrony, myocardial deformation, and diastolic function would identify patients who would benefit most from CRT. Method In 36 CRT patients, clinical evaluation and echocardiography were performed before and after CRT. Patients were classified into three subgroups according to their amount of response: echocardiographic responders, clinical responders, and nonresponders. Radial dyssynchrony and left ventricular (LV) global longitudinal, radial, and circumferential peak strain was assessed by speckle-tracking image. Diastolic function was quantified by conventional echocardiography. Result In addition to left bundle branch block, nonspecific intraventricular conduction disturbance with intraventricular dyssynchrony could also improve LV remodeling. Echocardiographic responders had better global longitudinal strain, global circumferential peak strain, and global radial strain at baseline which significantly increased at 12-month follow-up. An improvement in estimates of LV filling pressure and a decrease in mitral regurgitation and left atrial dimensions were observed only in echocardiographic responders to CRT. Patients with clinical but without echocardiographic response showed a significant improvement in atrioventricular (AV) synchrony and a nonsignificant improvement in other parameters. The nonresponder group did not improve the AV and intraventricular dyssynchrony. CRT could not improve restrictive filling pattern with normal filling time. Overall, those patients with AV and intraventricular dyssynchrony and those with best contractile function and short diastolic filling time of restrictive filling pattern at baseline demonstrated the greatest benefit from CRT. Conclusions Mechanical dyssynchrony, contractile function, and filling pattern are important determinants of the benefits in CRT.